Contrasting genomic properties of free-living and particle-attached microbial assemblages within a coastal ecosystem - Smith, Maria W.; Zeigler Allen, Lisa; Allen, Andrew E.; Herfort, Lydie; Simon, Holly M. (Frontiers in Microbiology, 2013)
The Columbia River (CR) is a powerful economic and environmental driver in the US Pacific Northwest. Microbial communities in the water column were analyzed from four diverse habitats: 1) an estuarine turbidity maximum (ETM); 2) a chlorophyll maximum of the river plume; 3) an upwelling-associated hypoxic zone; and 4) the deep ocean bottom. Three size fractions, 0.1-0.8, 0.8-3 and 3-200 μm were collected for each habitat in August 2007, and used for DNA isolation and 454 sequencing, resulting in 12 metagenomes of >5 million reads (>1.6 Gbp). To characterize the dominant microorganisms and metabolisms contributing to coastal biogeochemistry, we used predicted peptide and rRNA data. The 3- and 0.8-μm metagenomes, representing particulate fractions, were taxonomically diverse across habitats. The 3-μm size fractions contained a high abundance of eukaryota with diatoms dominating the hypoxic water and plume, while cryptophytes were more abundant in the ETM. The 0.1-μm metagenomes represented mainly free-living bacteria and archaea. The most abundant archaeal hits were observed in the deep ocean and hypoxic water (19% of prokaryotic peptides in the 0.1-μm metagenomes), and were homologous to Nitrosopumilus maritimus (ammonia-oxidizing Thaumarchaeota). Bacteria dominated metagenomes of all samples. In the euphotic zone (estuary, plume and hypoxic ocean), the most abundant bacterial taxa (≥40 % of prokaryotic peptides) represented aerobic photoheterotrophs. In contrast, the low-oxygen, deep water metagenome was enriched with sequences for strict and facultative anaerobes. Interestingly, many of the same anaerobic bacterial families were enriched in the 3-μm size fraction of the ETM (2-10X more abundant relative to the 0.1-μm metagenome), indicating possible formation of anoxic microniches within particles. Results from this study provide a metagenome perspective on ecosystem-scale metabolism in an upwelling-influenced river-dominated coastal margin.